Lightweight authentication protocols for wearable devices. (October 2017) - Das, Ashok Kumar; Zeadally, Sherali; Wazid, Mohammad
Abstract: In the wearable communication environment, wearable devices are used for various applications including fitbit flex tracks steps, sleep cycles, workout stats, and recording health-related sensitive information. The decreasing costs and increasing performance of Information Communication Technologies (ICTs) have made wearable devices more cost effective. Different types of wearable devices are being used today by citizens to improve their health and lifestyle. However, the data (such as health-related or movement data) generated from the user's daily activities is often private and therefore, ensuring the security and privacy of this data is important. First, we present some emerging trends of wearable devices followed by a discussion of the main security and functionality requirements along with the threats to the wearable communication environment. We then present a review of some of the recently proposed lightweight authentication protocols for wearable devices based on performance metrics such as computation cost and communication cost. We also compare these authentication protocols in terms of various security features they support. Finally, we discuss some future challenges in the area of security protocols for wearable devices that need to be addressed in the future.